Challenges of financing higher education in the Kingdom of Saudi Arabia: Taibah University is a model - Alharbi, Enas Moedh Almukhlafi (Journal of Educational and Psychological Sciences, 2025)
The objective of this research was to identify the challenges facing higher education funding in the Kingdom of Saudi Arabia and propose potential funding solutions, accomplished by reviewing the most significant global experiences along with the experiences of Saudi universities. The researcher employed a descriptive survey methodology, combining documentary and field studies, utilizing a questionnaire distributed to a random sample of 147 faculty members from the College of Education at Taibah University. The findings of the research revealed that the lack of accounting systems, which reduces transparency, ranked as one of the most significant challenges to higher education funding, with a high response rate, while the increasing demand for education was identified as a major challenge. Conversely, the scarcity of university research and studies on spending efficiency and university funding was ranked as the least significant challenge. Regarding the possible alternatives for funding higher education in Saudi Arabia, responses were rated as high, with averages ranging between 3.54 and 4.06 out of 5, indicating a high level of agreement. The most prominent suggestion was the investment in higher education institutions’ facilities to generate appropriate financial returns and transforming these institutions into productive universities. Meanwhile, the proposal of commercially marketing the products of higher education institutions received the lowest response, yet the level of agreement was still high, with a percentage of 63%. Based on the results, the study recommended the establishment of business and research incubators on a paid basis, drawing inspiration from leading global experiences in higher education funding and supporting more scientific research and studies that focus on rationalizing expenditures in higher education institutions.
Keywords: financing; financing higher education; higher education